Impact of bypass diode forward voltage on maximum power of a photovoltaic system under partial shading conditions - Teo, J.C.; Tan, Rodney H.G.; Mok, V.H.; Ramachandaramurthy, Vigna K.; Tan, Chia Kwang (Elsevier, 2020)
The maximum power of a photovoltaic system can reduce significantly under partial shading conditions. Bypass diodes can be used in photovoltaic systems to bypass the shaded photovoltaic modules during partial shading. The bypass diode possesses a forward voltage that introduces a voltage drop in the photovoltaic system upon activation. Therefore, the maximum power of a photovoltaic system can reduce further during partial shading due to the forward voltage of the bypass diode. This paper presents an investigation into the effect of bypass diode forward voltage on the maximum power of a photovoltaic system under partial shading conditions. The results indicated that the forward voltage of the bypass diode did not necessarily decrease the maximum power of the photovoltaic system. This depends on whether the maximum power is delivered at a lower or higher voltage. When the maximum power is delivered at a higher voltage, it is insusceptible to the forward voltage. Conversely, when the maximum power is delivered at a lower voltage, it is susceptible to the forward voltage. In the worst-case scenario, the forward voltage of the bypass diode reduced the maximum power of the photovoltaic system by 16.48%, which was already subject to partial shading loss. © 2019 Elsevier Ltd